Supplementation with dimethylglycine sodium salt improves lipid metabolism disorder in intrauterine growth-retarded pigs - Kaiwen Bai; Luyi Jiang; Tian Wang (Animal Nutrition)
This study aims to elucidate the mechanism of lipid metabolism disorder in intrauterine growth retardation (IUGR) pigs and the potential alleviating effects of dimethylglycine sodium salt (DMG-Na). A total of 60 male newborn piglets were selected for this study. Within each litter, one normal birth weight (NBW) male piglet (1.53 ± 0.04 kg) and two IUGR male piglets (0.76 ± 0.06 kg) were chosen based on their birth weight. The piglets were divided into three groups for the study: NBW pigs received a PBS gavage and a common basal diet (NBW-C group), IUGR pigs received the same PBS gavage and common basal diet (IUGR-C group), and IUGR pigs received a 70-mg DMG-Na gavage along with a common basal diet supplemented with 0.1% DMG-Na (IUGR-D group). At 150 d of age, all piglets underwent euthanasia by exsanguination following electrical stunning, after which plasma, liver, and longissimus dorsi (LM) samples were promptly collected. The IUGR-D group demonstrated improvements in plasma parameters (P < 0.05), with lower triglyceride and free fatty acid (FFA) values, and hormone levels (P < 0.05), with lower growth hormone, insulin, and homeostasis model assessment of insulin resistance values. Restoration of lipid metabolism was observed (P < 0.05), with lower triglyceride and FFA, and higher hepatic lipase and total lipase values in the liver, and lower triglyceride and FFA values in the LM. Mitochondrial ETC complexes showed increased levels (P < 0.05), including higher complex III values in the liver, and higher complex I, complex III, and complex V values in the LM. Enhanced levels of energy metabolites were noted (P < 0.05), with higher NAD+, NAD+/NADH, adenosine triphosphate, and mtDNA values, and lower NADH values in the liver and LM. Additionally, meat quality parameters showed improvement (P < 0.05), with higher pH 24 h and a∗ values, and lower drip loss 48 h, L∗, and b∗ values. The expressions of lipid metabolism and mitochondrial function-related genes and proteins were upregulated (P < 0.05) compared to the IUGR-C group. In conclusion, it was indicated that IUGR pigs experienced lipid metabolism disorders and diminished performance. However, supplementation with DMG-Na showed promise in mitigating these adverse physiological effects by safeguarding body tissues and modulating energy metabolism.